Evoluç\~ao do acesso de jovens à educaç\~ao superior no Brasil - Paulo Roberto Corbucci (Instituto de Pesquisa Econômica Aplicada (IPEA), 2014)
– This study aims to analyze the evolution of access to higher education in the cohort 18-24 years, which is considered the most adequate for this level of education. Initially, we question the use of this age group as a reference to measure the degree of access to this level of education in Brazil. Then, we analyze some factors that establish close relationship with attendance rates to higher education. In order to compare the situation of Brazil in the international context, a brief comparison is made with the evolution of access to higher education in Mexico. Finally, we present some conclusions about the variables associated with inequalities in access portrayed throughout the text, as well as pointing to one of the main limiting factors for the achievement of the target of net attendance rate of 33% set out in the bill of the National Plan of Education that is under discussion in National Congress.
Keywords: I21; I24; 330; access and potential demand for higher education; socioeconomic inequalities; regional inequalities